Public Sector Workers' Mental Health in Argentina: Comparative Psychometrics of the Perceived Stress Scale - Agustín Ramiro Miranda; Ana Veronica Scotta; Ana Lucía Méndez; Silvana Valeria Serra; Elio Andrés Soria (Korean Society for Preventive Medicine, 2020)
Objectives Given that Argentinian public-sector workers are highly exposed to stressful conditions, and that the psychometric properties of the widely used Perceived Stress Scale (PSS) should be evaluated in different settings, this work aimed to compare the psychometric properties of the Latin American Spanish PSS-10 and PSS-4 and to identify the optimal scale for stress assessment. Methods A sample of 535 participants was randomly divided into 2 groups to evaluate dimensionality by exploratory and confirmatory factor analyses. The reliability of both scales was also evaluated. Convergent validity was estimated using the Executive Complaints Questionnaire, the average variance extracted, and the composite reliability. Discriminant validity was based on the correlation with the Utrecht Work Engagement Scale and the phi-square correlation between the components. Results The factor analyses supported bidimensionality of the PSS-10 (stress and coping), which showed a better fit than the PSS-4. Moreover, the reliability of the PSS-10 was higher, whereas the PSS-4 did not achieve adequate values of internal consistency. The PSS-10 was also correlated significantly with all validation scales, and presented proper internal convergent and divergent validity. Conclusions The PSS-10 is a reliable and structurally valid instrument to measure perceived stress and coping in a Latin American Spanish-speaking population with high work demands, and the findings of this study expand our knowledge on the geographical and sociocultural applicability of the PSS.